The equality impact of the unemployment crisis - Kelly, Elish; Kingston, Gillian; Russell, Helen; McGinnity, Frances (Statistical and Social Inquiry Statistical Society of Ireland, 2015)
The extent of the Great Recession in Ireland is well documented. Real GDP fell by 10 per cent between 2008 and 2010 (Barrett and McGuinness, 2012). The impact that this large fall in economic activity had on the country’s labour market was severe, with Ireland’s overall unemployment rate increasing from 4.6 per cent in 2006 to 15 per cent in 2012, while the numbers in employment fell from 68.5 per cent to 58.8 per cent over the same time period. Long-term unemployment also increased considerably from 1.5 per cent in 2006 to 9.2 per cent in 2012. Fortunately, some modest economic growth since 2012 (see Duffy et al., 2014) has resulted in unemployment beginning to fall and increases in employment: by Quarter 1 2015, the unemployment rate stood at 9.9 per cent and the employment rate 62.2 per cent, while the long-term unemployment rate has fallen to 5.9 per cent.
Symposium on the Labour Market (read before the Society, 19th February 2015)
Keywords: 314.15